PREPARATION AND PROPERTIES OF POLYPROPYLENE AND PA 6 COMPOSITES REINFORCED WITH ARMENIAN TUFF STONE - Karnik Tarverdi; Zaruhi Madoyan (European Scientific Journal, ESJ, 2014)
The present paper discusses preparation, testing and possible uses of new composites, which consists of commodity and engineering polymers such as polypropylene (PP) and polyamide (PA6) reinforced with waste Armenian tuff stone powder. The paper will discuss extrusion and blending of the materials using co-rotating twin screw extruder with the inclusion of compatibiliser for enhancing the properties of the composite. The microstructure, thermal and mechanical properties of the composites have been examined following injection moulding of tensile test samples with a view of using these composites for added value applications.